Amazon is my hangout! Self-disclosure and community building in Amazon’s reviews - Fornaciari, Federica (AoIR Selected Papers of Internet Research, 2013)
This study investigates patterns of self-disclosure in Amazon reviews measuring the level of sensitive information that different users revealed. Informed by Goffman’s work on the “presentation of self in everyday life”, this study investigates sensitivity of information by using the software Linguistic Inquiry and Word Count (LIWC). Using a crawler we collected 3,485 reviews from Amazon, for six products. Sensitivity was measured through five main LIWC categories that include the following: pronouns, social processes, affective processes, biological processes, and personal concerns. As a result, Amazon reviewers in the sample collected disclosed significantly higher levels of sensitive information in these categories: family, humans, affect, positive emotions, negative emotions, sadness, cognitive mechanisms, concerns related to work, achievements, leisure and money. Results seem to suggest that users experience Amazon as a community built around people, whose participants often show their humanity, their offline social circles, their affective processes, their emotions, and their concerns.